Case Of Disclosure Of Human Smuggling Network By Police In Dumai In The Lens Of Immigration Crackdown - Fachrizza Sidi Pratama; Anindito R. Wiraputra (Journal of Law and Border Protection, 2019)
Globalization has an influence on the implementation of relations between countries, between peoples, and between individuals become closer, influenced and dependent so as to create a condition of the borderless world. This is reinforced by the emergence of a crime phenomenon that crosses the borders of a country, known as Transnational Organized Crime. One form of transnational crime that became the main discussion in this journal is Smuggling of Migrants or Human Smuggling conducted in the territory of Indonesia. The cases raised are implementation and handling, especially those that have been implemented by the Police of the Republic of Indonesia in Dumai in 2017 which will be based on the point of view of immigration enforcement.